THE RELATIONSHIP BETWEEN SELECTION OF FIRST COMPLEMENTARY FOODS WITH FOOD PREFERENCES IN INFANTS AND TODDLERS - Esty Puji Rahayu; Annif Munjidah (Siklus : Journal Research Midwifery Politeknik Tegal, 2020)
Giving complementary food at the right time is very beneficial for meeting the nutritional needs and growth and development of infants. However, if the child is difficult to eat or choose to eat, the child's growth will be disrupted It also becomes stressful for his parents. Food picking habits are included in the term food preference. In addition to being picky about food, rejection of certain foods is also included in this term. In this study, we want to know the relationship between First complementary food selection with Food Preference in infants and toddlers. The research design used is correlational analytic with a retrospective approach. The population is mothers who have babies and toddlers under the age of 5 years in the Rw 11 region of Jagir sub-district. The sampling technique uses purposive sampling technique. From data analysis with the Spearman test. in this study the selection of the first complementary food and Food Preference has a significant relationship with p value 0.044. It is expected that the results of this study will make mothers who have toddlers understand even more about choosing the right complemetary foodnamely with a complete menu that we feel we call a 4 star menu Keywords: complementary food, picky eater, food preference